The Influence of Swift Guanxi on Purchase Intention of Gen Z and Millennials on Shopee Live Streaming Users in Indonesia - Salsabila, Pavita Fitri; Trisnawati, Juliani Dyah; Megawati, Veny (Departemen Manajemen Fakultas Ekonomi dan Bisnis Universitas Negeri Malang, 2024)
This study aims to explore the influence of swift guanxi on purchase intention among Shopee live streaming users in Indonesia. Swift guanxi refers to interpersonal relationships that are formed quickly between buyers and sellers on e-commerce platforms. This study uses a quantitative approach with a survey method, involving 316 respondents from Gen Z and Millennials who actively use Shopee live streaming. The analysis model used includes validity and reliability tests with SPSS, as well as testing the influence between variables using PLS-SEM. The results of the analysis show that telepresence, flow, perceived informativeness, perceived responsiveness, and perceived likeability have a significant effect on swift guanxi, while guidance shopping and metavoicing do not have a significant effect. Swift guanxi is proven to have a significant effect on purchase intention and gift-giving intention. This study is expected to provide insight for business actors to understand the importance of swift guanxi in increasing consumer purchase intention on e-commerce platforms.